2002
DOI: 10.1086/339456
|View full text |Cite
|
Sign up to set email alerts
|

A Theory of Stochastic Harvesting in Stochastic Environments

Abstract: A theory of stochastic harvesting in stochastic environments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…It was straightforward that when fishing intensity was above a certain threshold (around 50% of the maximum value for both the eastern Skagerrak and Kattegat), the abundance of adult cod was depressed, irrespectively of the recruitment strength. Thus, the results of our study largely confirm recent theoretical applications and, as stated by Jonzén et al (2002b), call for a reconsideration of the role of harvesting as a stochastic process and potential source of population variability.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It was straightforward that when fishing intensity was above a certain threshold (around 50% of the maximum value for both the eastern Skagerrak and Kattegat), the abundance of adult cod was depressed, irrespectively of the recruitment strength. Thus, the results of our study largely confirm recent theoretical applications and, as stated by Jonzén et al (2002b), call for a reconsideration of the role of harvesting as a stochastic process and potential source of population variability.…”
Section: Discussionsupporting
confidence: 88%
“…However, it has been recently demonstrated that for several commercially exploited populations harvesting mortality can explain most of the population variability (i.e. Jonzén et al, 2002b). As highlighted by Jonzén et al (2002b) in a theoretical study, harvesting may explain a considerable proportion of the variation in population density if the mean harvest rate is high and the magnitude of its variance is comparable to or larger than that of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, by examining survival and yields over different timeframes and harvesting strategies this work presents a novel and a useful perspective on wild meat harvesting under uncertainty. Secondly, using a relatively simple analytical model such as the Beverton-Holt model provides certain advantages over stochastic simulation studies [53,66,67], such as more generalisable, robust conclusions that capture the most salient features of population dynamics useful for exploring system sensitivity to different parameter values and guiding more detailed simulation studies of particular situations [32,65]. Other population models could easily be used instead of the Beverton-Holt model [68], and employing different models would allow model uncertainty (ignored here) to be addressed.…”
Section: Plos Onementioning
confidence: 99%
“…External forcing may also include anthropogenic sources as well as environmental. Under the right conditions, variable fishing pressure has been shown to drive perturbation in the abundance of exploited populations directly (Jonzen et al, 2001(Jonzen et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%